LEXICAL BORROWING IN NEOLOGY DIMENSION OF CONTEMPORARY FRENCH - Heiko Тetiana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with the state of neologism processes and the dynamics of borrowing in the modern French language for the period 2015-2018, examines the theoretical foundations of the above-mentioned linguistic phenomena and a justified method of researching various aspects of neologisms and the results of the analysis of borrowings. The use of the Néoveille platform made it possible to semi-automatically detect, describe linguistically, and trace the temporal evolution of neologisms from three complementary points of view: temporal, linguistic, and socio-pragmatic. In the temporal aspect, it is important to distinguish three moments in the life of neologisms: appearance, possible distribution and possible lexicalization. Linguistic approach allows to describe formation mechanisms, as well as combinatorial and distributive properties of loanwords. A socio-pragmatic point of view makes it possible to identify the places where neologisms are used. By applying these points of view, a system capable of semi-automatically detecting lexical innovation and tracing its evolution on a large dynamic corpus was modeled. Borrowings make up about 6 % (or 1,429 tokens) of innovations in modern French [3]. About a thousand xenisms should be added to this number, as well as a significant number of other formations from borrowed bases. Over 90 % of these loanwords are of Anglo-American origin, while xenisms show more linguistic diversity. The spheres of human activity that are most open to borrowing are fashion, sports, technology, and the economy, and among the resources, the women’s press, Parisian magazines, and the yellow press are the most fruitful. Borrowings, like all neologisms, are more than 75 % hapax or quasi-hapax, or rather neologisms with low or very low diffusion. The appearance of Anglo-American borrowings is explained both by the needs of the nomination and motivated by the prestige of the English language, which in recent decades,especially with the advent of digital communication, has acquired the status of a second integrated language used by the French in private and professional life. English plays the same role for most modern languages. This global lingua franca is an instantly accessible resource for lexical innovation and a provider of productive morphosyntactic patterns, usually of a synthetic nature, actively implemented in French. The study of neologisms of higher frequency shows that the popularity of social networks and some social practices contributed to the emergence of borrowings in many fields. The described parameters made it possible to present cases of diffusion of borrowings, not only through stabilized repetitions, but also to state certain linguistic phenomena, in particular, integration into the morphogrammatic subsystem of the French language. __________ Refernces: • Cartier, Emmanuel. «Emprunts en français contemporain: étude linguistique et statistique à partir de la plateforme Néoveille.» L’emprunt en question(s): conceptions, réceptions, traitements lexicographiques (2019), https://hal.archives-ouvertes.fr/hal-02537344, Submitted on 8 Apr 2020. • Cartier, Emmanuel, Sablayrolles, Jean-François, Boutmgharine, Najet, Humbley, John, Bertocci, Massimo, Jacouet-Pfau, Christine, Kubler, Natalie et Tallarico, Giovanni. «Détection automatique, description linguistique et suivi des néologismes en corpus : point d’étape sur les tendances du français contemporain.» Actes du Congrès Mondial de Linguistique française: SHS Web of Conferences (Mons 9-13 juillet 2018), 46, - P. .08002. ⟨1051/shsconf/20184608002⟩. ⟨hal-03086023 • Cartier, Emmanuel, Viaux, Julie. «Étude de la pénétration des anglicismes de type N ou ADJ(-) Ving à partir d’un corpus contemporain journalistique: les exemples de bashing et shaming en français contemporain.» Folia Litteraria Romanica (2018): 11-34. • Chadelat, Jean-Marc. Valeur et fonctions des mots français en anglais à l’époque contemporaine (Editions L’Harmattan, 2000), 228. • Chesley, Paula, Baayen, R. Harald. «Predicting new words from newer words: Lexical borrowings in French.» Linguistics # 48(6) (2010): 1343-1374. • Dubois, Jean. «Étude sur la dérivation suffixale en français moderne et contemporain.» Librairie Larousse (1962), 118. • Guilbert, Louis. La créativité lexicale (Paris: Larousse, 1975), 127. • Rogers, Everett. The Diffusion of Innovations, Fifth Edition (The Free Press, New York, 2003), 570. • Sablayrolles, Jean-François. «Neologia une base de données pour la gestion des néologismes.» Actes del I congrès internacional de neologia de lês lengues romàniques (Barcelone: UPF/IULA, 2010): 757-766. • Sablayrolles, Jean-François. La néologie en français contemporain, examen du concept et analyse de productions néologiques récentes, - coll. Lexica Mots et Dictionnaires (Champion, 2000), 589. • Sablayrolles, Jean-François. «Néologie, classes d’objets et extraction automatique.» Actes du Congrès Cineo (néologie des langues romanes) de Barcelone (7-10 mai 2008) (2010): 143-149. • Sablayrolles, Jean-François. Les néologismes. Créer des mots français aujourd’hui, Petits guides de la langue française29 (Paris: Garnier et Le Monde, 2017), 99. • Sablayrolles, Jean-François, Prévost, Jean. Les néologismes (Presses Universitaires de France-PUF, Collection Que sais-je ?, 2019), 128. • Schmid, Hans-Jörg. New words in the mind: Concept-formation and entrenchment of neologisms. Anglia #126 (1) (2008): 1-36. • Schmid, Hans-Jörg. Entrenchment and the Psychology of Language Learning: How We Reorganize and Adapt Linguistic Knowledge (Walter de Gruyter GmbH & Co KG, 2016), 475.